2020
DOI: 10.2147/ijgm.s261718
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Evaluation for the Role of High-Sensitivity C-Reactive Protein in Combination with D-Dimer and Wells Score Probability Test to Predict the Incidence of Deep Vein Thrombosis Among Cancer Patients</p>

Abstract: Background Deep vein thrombosis (DVT) is a frequent complication in cancer patients and is the second leading cause of death. The high level of C-reactive protein (CRP) is an acute phase reactant that induces tissue factor (TF) expression in monocytes, smooth muscle cells, and endothelial cells. The CRP level positively correlates with the incidence, extension, and volume of thrombus. TF expression triggers the coagulation system including the formation of thrombin and circulating fibrin such as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
5
0
2
Order By: Relevance
“…21,22 A study by Setiawan et al reported that a combination of D-dimer (≥5030 μg/L), hs-CRP (≥51.05 mg/L) and Wells score ≥3 can predict DVT incidence in cancer patients. 23 The results of this study support the notion that age and D-dimer are important factors in the development of DVT; thus, cancer patients who are of older age with high D-dimer level can be considered at high risk of thrombosis and could be candidates for thromboprophylaxis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…21,22 A study by Setiawan et al reported that a combination of D-dimer (≥5030 μg/L), hs-CRP (≥51.05 mg/L) and Wells score ≥3 can predict DVT incidence in cancer patients. 23 The results of this study support the notion that age and D-dimer are important factors in the development of DVT; thus, cancer patients who are of older age with high D-dimer level can be considered at high risk of thrombosis and could be candidates for thromboprophylaxis.…”
Section: Discussionsupporting
confidence: 82%
“… 21 , 22 A study by Setiawan et al reported that a combination of D-dimer (≥5030 μg/L), hs- CRP (≥51.05 mg/L) and Wells score ≥3 can predict DVT incidence in cancer patients. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Regarding CAT, several biomarkers have been assessed for prediction of primary VTE risk, but CRP has not been studied as extensively as other biomarkers such as D-dimer, leukocyte and platelet count. A small study of 35 patients found that the combination of hsCRP, D-dimer and the clinical Wells score could predict the incidence of acute DVT in cancer patients ( 79 ). A study of 507 cancer patients in Germany, of which 60 developed a new VTE, found that those with VTE had higher circulating CRP levels in the 30 days prior to the VTE episode than those without any VTE in the follow up period ( 80 ).…”
Section: Crp As a Predictor Of Cancer-associated Vtementioning
confidence: 99%
“…Deep Vein Thrombosis (DVT) is a disease characterized by the formation of a thrombus and accompanied by an inflammatory response in the deep veins, which usually occurs in the lower extremities, with clot formation starting in the deep calf veins and spreading proximally (Azzahro & Mahmuda, 2020;Stubbs et al, 2018;Yokoi et al, 2017). Thrombus that forms in the veins, is generally also found in the pelvic area (Setiawan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%